Implementation of Interactive PowerPoint Media on Collaborative Skills in Madrasah Ibtidaiyah - Hamida, Silvi Imroatul; Nurdyansyah, Nurdyansyah (research, training and philanthropy institution Natural Aceh, 2024)
This study aims to analyze whether this interactive PowerPoint presentation can improve students' ability to collaborate with their friends in class. Data collection techniques used were observation, interviews, and documentation. Data analysis used in this research is the Miles & Hiberman model, which consists of stages 1) data reduction, 2) data presentation, and 3) conclusion drawing and classification. This study found that there are still some teachers who rarely apply technology-based learning media, such as interactive PowerPoint media, in the learning process in the classroom, causing boredom and a lack of enthusiasm for learning. However, with the application of interactive PowerPoint media, students are increasingly excited and interested in the learning process, so it has a good impact on learning activities, which is characterized by an increased sense of student responsibility for the tasks assigned and fluency in communication. The application of interactive PowerPoint media by the homeroom teacher of grade 4 SDN Simoketawang in the learning process is able to improve the collaborative attitude of students in the classroom in accordance with collaborative indicators. The achievement of collaborative indicators in students has implications for the increase in student scores, which were originally below the minimum completeness criteria (KKM) to an average above the minimum completeness criteria (KKM).